UNIT 13.14 Flow Cytometry of Extracellular Vesicles: Potential, Pitfalls, and Prospects. Issue 1 (1st July 2015) - Nolan, John P.
Abstract : Evidence suggests that extracellular vesicles (EVs) can play roles in physiology and pathology, providing impetus to explore their use as diagnostic and therapeutic targets. However, EVs are also small, heterogeneous, and difficult to measure, and so this potential has not yet been realized. The development of improved approaches to EV detection and characterization will be critical to further understanding their roles in physiology and disease. Flow cytometry has been a popular tool for measuring cell‐derived EVs, but has often been used in an uncritical manner in which fundamental principles and limitations of the instrument are ignored. Recent efforts to standardize procedures and document the effects of different methodologies have helped to address this shortcoming, but much work remains. In this paper, I address some of the instrument, reagent, and analysis considerations relevant to measurement of individual EVs in flow, with the aim of clarifying a path to quantitative and standardized measurement of these interesting and potentially important biological nanoparticles. © 2015 by John Wiley & Sons, Inc.